2012
DOI: 10.1038/nchembio.767
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics implicates altered sphingolipids in chronic pain of neuropathic origin

Abstract: Neuropathic pain is a debilitating condition for which the development of effective treatments has been limited by an incomplete understanding of its chemical basis. We show by using untargeted metabolomics that sphingomyelin-ceramide metabolism is altered in the dorsal horn of rats with neuropathic pain and that the up-regulated, endogenous metabolite N,N-dimethylsphingosine induces mechanical hypersensitivity in vivo. These results demonstrate the utility of metabolomics to implicate unexplored biochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
170
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 24 publications
6
170
0
Order By: Relevance
“…Exogenous application of neutral sphingomyelinase or C 2 -ceramide increases TTX-resistant sodium currents in the soma of primary sensory neurons (54). In the spinal dorsal horn, neutral sphingomyelinase and ceramide levels are increased in neuropathic rats induced by nerve injury (16). Suppression of ceramide production in the spinal dorsal horn ameliorates neuro- pathic pain, which is accompanied by decreased microglial activation in the spinal dorsal horn (17).…”
Section: Role Of Ceramide In Pathologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous application of neutral sphingomyelinase or C 2 -ceramide increases TTX-resistant sodium currents in the soma of primary sensory neurons (54). In the spinal dorsal horn, neutral sphingomyelinase and ceramide levels are increased in neuropathic rats induced by nerve injury (16). Suppression of ceramide production in the spinal dorsal horn ameliorates neuro- pathic pain, which is accompanied by decreased microglial activation in the spinal dorsal horn (17).…”
Section: Role Of Ceramide In Pathologicalmentioning
confidence: 99%
“…Previous studies showed that levels of ceramide in the spinal dorsal horn are increased in neuropathic animals following nerve injury (16,17) or in morphine-tolerant rats (18). Ceramide is a potent proinflammatory sphingolipid that is generated by hydrolysis of sphingomyelin on the membrane by acid or neutral sphingomyelinase (19).…”
mentioning
confidence: 99%
“…Thus, to discover novel plasma metabolite biomarkers for VTE risk, we performed liquid chromatography-mass spectrometry (LC-MS)-based untargeted metabolomics in a pilot study to analyze plasma metabolites without any specific targeting of known metabolites (supplemental Figure 1A, available on the Blood Web site). [2][3][4][5][6] One lipid metabolite family, namely, acylcarnitines (ACs), exhibited association with VTE. When AC lipids were tested in coagulation assays for any potential causality relationship, the novel anticoagulant activity of ACs was discovered and was shown to involve targeting of factor Xa.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a relatively recent discipline dedicated to the global study of endogenous metabolites in tissues and biofluids [10][11][12]. Considerable evidence on the identification of the link between endogenous metabolites and symptoms has been obtained from studies using non-targeted metabolomics in the dorsal horn of rats with neuropathic pain [13]. A non-targeted metabolomic approach may be useful to identify EF-induced biomarkers.…”
Section: Introductionmentioning
confidence: 99%